Study of the effect of bacteria of the genus Pseudomonas on the growth and toxin production of the fungus Fusarium graminearum in vitro - V. F. Tolkach; Yu. G. Volkov; N. N. Kakareka; M. R. Aliev; M. Yu. Shchelkanov (Юг России: экология, развитие, 2024)
Aim. To study the potential of bacteria strains P. chlororaphis BZR 245‐F and Pseudomonas sp. BZR 523‐2 to inhibit the growth of Fusarium ear blight pathogens through the example of the fungus F. graminearum and to reduce the accumulation of deoxynivalenol (DON) and zearalenone (ZEN) in vitro.   Materials and Methods. Antifungal metabolites of Pseudomonas bacteria were analysed by thin layer chromatography and bioautography. An experiment on the effect of liquid culture and supernatant of bacteria on the growth and toxin production of the fungus F. graminearum in vitro was carried out on wheat grain. Analysis of grain for mycotoxins was carried out by HPLC‐HRMS.   Results. The ability of strains P. chlororaphis BZR 245‐F and Pseudomonas sp. BZR 523‐2 to produce antifungal metabolites was found, while inhibiting the growth of the fungus F. graminearum 60318 in vitro. The content of DON decreases both under the action of the liquid culture and supernatant of P. chlororaphis BZR 245‐F bacteria by 60 % and 70 %, respectively, and the liquid culture and supernatant of Pseudomonas sp. BZR 523‐2 bacteria by 75 % and 90 %, respectively. The accumulation of ZEN is also significantly suppressed under the influence of liquid cultures and supernatants of bacterial strains. The amount of ZEN decreases under the influence of liquid culture and supernatant of P. chlororaphis BZR 245‐F bacteria by 80 % and 95 %, respectively. Liquid culture and supernatant of Pseudomonas sp. BZR 523‐2 bacteria inhibited the accumulation of ZEN by 60 % and 84 %, respectively.   Conclusion. The results obtained through the study of the effect of liquid cultures and supernatants of P. chlororaphis BZR 245‐F and Pseudomonas sp. BZR 523‐2 strains on the growth and toxin production of the fungus F. graminearum 60318 in vitro allow us to consider these strains as potential producers of effective biofungicides against toxin‐producing fungi. Further studies of these bacterial strains in vitro and in vivo on plants are needed.